Communism and Revolution : The Strategic Uses of Political Violence - Black, Cyril E. (Cyril Edwin), 1915-1989; Thornton, Thomas Perry (Book collections on Project MUSE., 1964)
After a historical survey of communism and its revolutionary doctrines, the authors study the legacy of World War II focusing on Eastern Europe, South east Asia, Vietnam, and Korea. Finally they examine evolving communist strategies for revolution focusing on Asia, the Middle East, Africa, et al.